The Role of the Relationship Between Globalization and Religion in Society (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The processes of globalization have significantly influenced various dimensions of social life, including religious beliefs and practices. In many societies, the advancement of global communication, migration, and economic integration has brought diverse religious traditions into closer contact, altering their role and perception within communities. However, a clear understanding is still lacking regarding how this relationship between globalization and religion concretely manifests in the daily life of societies and what social functions it fulfills. This study explores the societal significance of the relationship between globalization and religion, focusing on the mutual influence they exert and their role in shaping collective social behavior. The findings indicate that while globalization introduces universal values and secular frameworks, religion continues to act as a moral compass and cultural anchor within society. This interaction creates a space where both forces can coexist, negotiate, or even conflict, influencing societal stability and identity. The study provides an integrated perspective on how religion and globalization are not isolated or opposing domains but rather intertwined elements within the social structure. These insights contribute to a deeper academic and practical understanding of how societies can navigate cultural preservation and global integration simultaneously, making this relationship a critical factor in social development and policy-making.